Factors influencing surface water accumulation in beaver pond complexes across the Western United States - Luwen Wan; Emily Fairfax; Kate Maher (Communications Earth & Environment)
Abstract North American beavers (Castor canadensis) build dams and ponds that alter streamflow, enhance floodplain water storage, and provide refugia during droughts and wildfires. However, drivers of pond area variability remain poorly understood. Here, we quantified the influencing factors that drive pond area and dam length variations using an explanatory modeling approach, after mapping surface water area of beaver ponds and creating beaver pond complexes. Mapped area correlated well with manual delineations (r2 = 0.89), and additive pond area and dam length across 87 complexes followed a significant log-log scaling relationship. Dam length was the strongest covariate of pond area, while woody vegetation height and stream power index were also influential; together, these covariates explained 74% of the variation. Our results provide an empirical foundation to inform site selection and prioritization for beaver restoration, supporting watershed management, climate resilience and ecological conservation strategies in regions with comparable data availability and landscape characteristics.